GammaV EOS for Detonation Products - Partom, Yehuda (European Journal of Applied Sciences, 2023)
The standard way to start the derivation of an equation of state for detonation products is by defining a trial function Ps(V) along the principal isentrope of the products (where Ps is pressure and V is specific volume), with parameters to be determined from a cylinder expansion test. If that specific function turns out not to be good enough, a different function needs to be tried. We propose here a different approach which is to use instead the function gs(V), where gs is the adiabatic gamma along the principal isentrope, as defined by Eq. (2) below. By choosing gs we don’t have to assume the form of the function from the outset. Instead, we define the function by a set of points (n≥4), and we’re able to define the amplitudes of these points recursively. In what follows we first write down the equations for determining the values of gsi for the specific volumes Vi, and then work out an example with n=4. We show that even for n=4 the reproduction of test data is quite good, and also that the results are not sensitive to the exact choice of the values of Vi.